2017
DOI: 10.1103/physreva.95.022507
|View full text |Cite
|
Sign up to set email alerts
|

Scalar-pseudoscalar interaction in the francium atom

Abstract: Fr atom can be successively used to search for the atomic permanent electric dipole moment (EDM) [Hyperfine Interactions 236, 53 (2015); Journal of Physics: Conference Series 691, 012017 (2016)]. It can be induced by the permanent electron EDM predicted by modern extensions of the standard model to be nonzero at the level accessible by the new generation of EDM experiments. We consider another mechanism of the atomic EDM generation in Fr. This is caused by the scalar-pseudoscalar nucleus-electron neutral curre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 69 publications
4
52
0
Order By: Relevance
“…In standard coupled cluster applications the virtual space cutoff is usually set at around 30 a.u., at which point saturation of most properties with respect to the correlation space size is reached (in particular when core electrons are excluded from the correlation procedure). However, it was found that inclusion of the high lying virtual orbitals is important for the correlation of the core electrons for parity violating properties [47,62]. We thus set the cutoff of the virtual space to 2000 a.u.…”
Section: Virtual Space Cutoffmentioning
confidence: 99%
“…In standard coupled cluster applications the virtual space cutoff is usually set at around 30 a.u., at which point saturation of most properties with respect to the correlation space size is reached (in particular when core electrons are excluded from the correlation procedure). However, it was found that inclusion of the high lying virtual orbitals is important for the correlation of the core electrons for parity violating properties [47,62]. We thus set the cutoff of the virtual space to 2000 a.u.…”
Section: Virtual Space Cutoffmentioning
confidence: 99%
“…These two quantities cannot be measured, and are instead obtained from sophisticated molecular structure calculations in Refs. [25][26][27][28][29] for ThO and [30][31][32][33] for HfF + . The current values of the frequency are reported in [6,7]: The electron EDM and the NSID interactions arise from new physics beyond the Standard Model (BSM).…”
Section: Cp Violation In Polar Molecule Systemmentioning
confidence: 99%
“…In Refs. [19,50] we suggested to combine the two-step approach and the direct relativistic Dirac-Coulomb(-Gaunt) approach to take advantages of both approaches.…”
Section: Electronic Structure Calculation Detailsmentioning
confidence: 99%